Workaholism Sebagai Mediator Antara Stres Keuangan Dan Strategi Bertahan Hidup Generasi Sandwich - Meli Nurjannah; Erwanto Erwanto; Andi Thahir (Jurnal Ilmiah Global Education, 2026)
This study aims to understand how workaholism mediates financial stress and the adaptive strategies of the sandwich generation, and how Islamic values ​​influence the meaning and justification of this behavior. This study uses a qualitative approach with a phenomenological method to explore in depth the subjective experiences of individuals in interpreting financial stress and the urge to overwork. Primary data were obtained through in-depth interviews with participants who met the criteria for the sandwich generation, while secondary data were sourced from academic literature, documents, and relevant previous studies. This study analysis uses the Transactional Model of Stress and Coping theory by Lazarus and Folkman and the Religious Coping theory by Kenneth Pargament. These two theories were chosen because they are able to explain how individuals deal with economic stress through two main approaches: problem-focused coping through hard work and emotion-focused coping through spiritual values ​​such as tawakal (trust), patience, and contentment (qana'ah). This study is expected to contribute to the psychological and religious understanding of workaholism behavior in the sandwich generation, while also enriching scientific studies on the balance between economic responsibility, spirituality, and mental health in the context of Indonesian culture.